2020
DOI: 10.1101/2020.10.09.333658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of prophages into CRISPR loci remodels viral immunity inStreptococcus pyogenes

Abstract: SummaryCRISPR loci are composed of short DNA repeats separated by sequences that match the genomes of phages and plasmids, known as spacers. Spacers are transcribed and processed to generate RNA guides used by CRISPR-associated nucleases to recognize and destroy the complementary nucleic acids of invaders. To counteract this defense, phages can produce small proteins that inhibit these nucleases. Here we demonstrate that the ΦAP1.1 temperate phage utilizes an alternate approach to antagonize the type II-A CRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Their relatively higher occurrence on plasmids could indicate that CRISPR-Cas systems erode faster on plasmids, or that orphan components are recruited and/or selectively maintained to perform important, but as yet unknown, biological functions. Orphan CRISPR arrays could, for instance, employ host Cas machinery in trans (Almendros et al, 2016;Deecker and Ensminger, 2020) or facilitate plasmid chromosome integration via recombination between plasmid and host-encoded CRISPRs (Varble et al, 2019(Varble et al, , 2020. On the other hand, the higher proportion of orphan components may be an artefact of CRISPR-Cas prediction tools unable to detect a conceivably greater diversity of uncharted (sub)types across plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…Their relatively higher occurrence on plasmids could indicate that CRISPR-Cas systems erode faster on plasmids, or that orphan components are recruited and/or selectively maintained to perform important, but as yet unknown, biological functions. Orphan CRISPR arrays could, for instance, employ host Cas machinery in trans (Almendros et al, 2016;Deecker and Ensminger, 2020) or facilitate plasmid chromosome integration via recombination between plasmid and host-encoded CRISPRs (Varble et al, 2019(Varble et al, , 2020. On the other hand, the higher proportion of orphan components may be an artefact of CRISPR-Cas prediction tools unable to detect a conceivably greater diversity of uncharted (sub)types across plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…and 5 Acr proteins against the subtype II-C CRISPR-Cas system. [18][19][20] Structural and mechanistic studies revealed that type II Acrs inhibit their host Cas9 proteins through diverse mechanisms. They occupy the protospacer adjacent motif interaction site of Cas9 to compete with target DNA binding, 21,22 block the active site of the Cas9 nuclease domain, 23 induce nonfunctional Cas9 dimerization, 24,25 and cause Cas9 degradation in cell culture.…”
Section: Self-association and Interaction Of Acriic2mentioning
confidence: 99%